Clarifying the importance of the running film to the ultra-low wear of the polymer composite by eliminating its individual effect. (February 2023) - Lin, Zhibin; Zhang, Ke; Ye, Jiaxin; Gao, Bingzhao; Tao, Peng; Zhang, Zhihui
Abstract: Polytetrafluoroethylene (PTFE) composites with suitable fillers can exhibit ultra-low wear via transfer and running films formation and the prevention of matrix removal. However, they are often generated simultaneously, thereby making it difficult to distinguish their individual effects. In the present study, dual-pin-on-disk (DPOD) friction pairs are used to tailor the combination of different functions, so that the individual effects of the running and transfer films are identified. The results show that the running film formed on the worn polymer surface is indispensable for achieving ultra-low wear. The high-quality transfer film formed on the counterpart steel surface only slightly improves the wear performance individually, whereas ultra-low wear rates are achieved via the synergistic effect of the running and the transfer films. Highlights: The effect of the running film was eliminated by a dual-pin-on-disk friction pair Severe wear occurs without the running film, even a quality transfer film was formed. The low wear relies on the synergistic effect between the running and transfer films